Perceptions of Local Tourists, Attitudes and Willingness to Visit Local Destinations: A Destination Image Case - Eugine Tafadzwa Maziriri; Kamantha Govender; Tinashe Chuchu (Universitas Muria Kudus, 2021)
The paper made use of predictor variables to highlight relationships in tourism, these are: perceptions of local residents towards tourists and destination image; to identify how these predictors are relative to the mediator variable, attitudes of local residents towards tourists; which then led to the outcome variable, tourist’s willingness to visit a destination. Respondents were selected by means of non-probability sampling. A conceptualised model was developed to measure the variables adapted to the research study. The researcher conducted field research at The University of Witwatersrand, which included 270 respondents, currently registered at the university. The data set was analysed by employing SPSS and Amos 24 through Structural Equation Modelling (SEM). The results of the research confirmed that the attitudes of local residents had a stronger relationship than the perceptions of local residents towards tourists; influencing tourists’ willingness to visit a destination. This implies that tourists will visit a destination based on how they are treated by local residents, instead of how local residents perceive tourists.